2011
DOI: 10.1007/s12603-010-0297-1
|View full text |Cite
|
Sign up to set email alerts
|

The interrelationships among albumin, nutrient intake, and inflammation in elderly recuperative care patients

Abstract: Among elderly patients admitted to a TCU, inflammation appears to be a more powerful determinant of albumin and its change during the hospitalization than is nutrient intake. Further study is needed to prove causality and to determine whether the relative importance of inflammation on the albumin concentration diminishes with more prolonged periods of observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…According to the researches into the phenomenon of low-level of serum albumin in those diseases, abnormal metabolism of albumin led by inflammation response may be an important reason for that, as well as a low intake of albumin [19]. The mechanism is not clear yet, however, IL-6 and other inflammatory cytokines may play an important role in it [11, 18].…”
Section: Discussionmentioning
confidence: 99%
“…According to the researches into the phenomenon of low-level of serum albumin in those diseases, abnormal metabolism of albumin led by inflammation response may be an important reason for that, as well as a low intake of albumin [19]. The mechanism is not clear yet, however, IL-6 and other inflammatory cytokines may play an important role in it [11, 18].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature there is some evidence that ghrelin production and sensitivity is altered during aging, and it may be one of the potential explanations of the beginning of the phenomenon of anorexia of aging. Moreover, leptin and inflammation appear to be potential determinants of nutritional status [50], [51]. In our sample the lack of correlation between eating patterns and cytokines and ghrelin may be due to the large variability in measurements of circulating leptin and ghrelin concentrations, perhaps reflecting the heterogeneity of older persons living in different settings.…”
Section: Discussionmentioning
confidence: 77%
“…Sullivan’s study found that inflammation appears to be a more powerful determinant of albumin, particularly CRP, and IL-6, and its change during the hospitalization than is nutrient intake in elderly patients admitted to a TCU [21]. Another study found, TNF-α, IL-10, and markers of oxidative stress were in negative correlation with HDL cholesterol and albumin.…”
Section: Discussionmentioning
confidence: 99%